Single-Well Dynamic Permeability Splitting Algorithm and Classification Evaluation: A Case Study of a Super-Thick Carbonate Reservoir in the Middle East - Cao, Peng; Wang, Yongjun; Qiao, Zhanfeng; Zhu, Guangya; Su, Haiyang; Shao, Guanming; Gong, Jie; Deng, Haiyang (Frontiers in Energy Research, 2022)
The permeability interpretation accuracy of single wells in Middle East super thick carbonate reservoir can hardly meet the actual demand of water injection development. Therefore, in this paper, a split iterative algorithm to calculate single well segmental dynamic permeability and SPI (specific production index) is developed based on the dynamic and static well test, PLT (production log test), production test and logging interpretation data . Moreover, the dynamic permeability classification evaluation index was optimized. The detailed steps are: ① Split the liquid supply of a single well according tp PLT; ② For some production intervals, apply the log interpretation data to do the second iteration splitting of formation coefficient and fluid supply; ③ Calculatethe proportion of liquid supply in the stratification section based on the calculation results of step 1 and step 2; ④ Divide the total formation coefficient of well test interpretation based on the calculation results of step 3; ⑤ Calculate The dynamic permeability and SPI. The research results show that the dynamic permeability and SPI of a single well are accurate to the scale of one meter from the original several meters to tens of meters, which can better meet the needs of water injection development. In addition, The SPI can be used as an important index for permeability classification evaluation. Taking the Mishrif formation reservoir in Halfaya oilfield as an example, the lower permeability limit of MB1-2 high-permeability layer is 200mD, and the lower specific production index limit is 0.35 bbl /( d·m·psi ), which provides a dynamic basis for the identification of high permeability layers in this reservoir. This method provides a new idea for the identification of high permeability streaks. Moreover, This method can provide scientific basises for the correction of permeability attribute model, optimization of water injection plan, optimization of single well completion cementing scheme and water coning control, which can be popularized and applied in the same type of reservoirs.